Practical Guidelines for Water Percolation Capacity Determination of the Ground - Brenčič, Mihael (Geologija, 2011)
Determination of water infiltration capacity of ground soils and rocks represents important part of design and construction procedures of the facilities for the infiltration of clean precipitation water. With their help percolation capacity of ground as well as response of the infiltration facilities to the inflowing precipitation water is estimated. Comparing to other in situ hydrogeological tests they can be understood as simple. However, in every day’s practice several problems during their on site application and desk interpretation can arise. Paper represents review of existing practical engineering procedures during the performance of percolation tests. Procedures are described for the borehole and shaft percolation tests execution and calculation theory for stationary and non-stationary percolation tests are given. Theory is illustrated with practical exercises. Interpretations of typical departures from theoretical presumptions according to Hvorslev test of non-stationary test are illustrated.